ARAL REGIONINDA EKOLOGIYALIQ QA`WIPSIZLIKTIN` ALDIN ALIWDIN` TIYKARLARI - Jumamuratov, A.; Jumamuratova, B.A. (SCIENCE and SOCIETY, 2016)
The article deals with one of the actual problems – the prevention of ecological crisis in the zone of the Aral seaside. The author of the article gives some important information characterizing the ecological crisis in the region of the Aral seaside. There is the description of the main trends in the establishment of ecological security in the region.
Keywords: the Aral sea; ecology; atmosphere; ground; water; environement; pollution; ecological crisis; zone; prevention; protection